Improving the efficiency of educational technologies in a military higher education institution on the basis of the integrative potential of didactics - Taubaeva, Sharkul; Maxutova, Irina; Shagiyev , Mirkhat (Pedagogy and Psychology, 2021)
This article presents the genesis of the development of the higher educational space of the Republic of Kazakhstan, considers the positions of the authors on the holistic theory of learning, contradictions of modern pedagogy. The introduction of educational technologies into the training system does not lose its relevance. This is due primarily to the fact that practice and social demand do not reduce, but, on the contrary, increase the requirements for teachers. Practice indicates that training through the using of innovative didactics allows integrating educational technologies and increasing its effectiveness. During recent years, it has been done a lot to develop innovative didactics and the use of educational technologies to improve the educational process; this can be clearly seen especially in the process of improving students’ assimilability of theoretical material. Teachers of a higher, special educational institution need to master the innovative didactics purposefully and assertively of both its theoretical basis and its practical component expressed in intensive and interactive learning technologies: games, trainings, cases, game design, creative techniques and many other teaching techniques, because they develop the basic competence and multicompetence of the teacher. The teacher of a higher, special educational institution should have the skills and abilities necessary for the profession, which create the prerequisites for psychological readiness to introduce intensive training technologies into real practice.